A Review on Technologies for Group-Aware Malayalam Conversational AI - Husaima Mailanchy T K,; Suha Narghees A S,; Taniya T S,; Vishnu M S,; Dr. L.C. Manikandan, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This review paper explores the foundational technologies required to develop a group-aware Conversational AI for the Malayalam-English bilingual community. The objective of the project is to create an AI system capable of interacting naturally in group settings, dynamically recognizing and responding to multiple speakers in real-time. The key components of this system include voice separation, which isolates individual speakers’ voices in noisy environments, speech-to-text (STT), which accurately transcribes Malayalam speech that may contain English phrases, and text-to-speech (TTS), which synthesizes natural-sounding speech in Malayalam-English conversational patterns. This review covers recent advancements in each of these three areas by evaluating three core papers for each technology. Through this review, we aim to understand the current capabilities of these technologies and how they can be applied to build an accessible, scalable Conversational AI that bridges the language gap for Kerala’s linguistically diverse population.
Keywords: Conversational AI; Voice Separation; Speech-to-Text; Text-to-Speech; Malayalam-English; Multimodal Processing; Natural Language Processing; Bilingual Communication